Islam and family planning - United Nations (Asia-Pacific Population Journal, 1987)
The world’s 1.2 billion Muslims comprise about 20 per cent of the total population of the world. The majority of Muslim populations have high fertility rates coupled with high infant, child and maternal mortality, and low rates of life expectancy. As a result, close to 50 per cent are below 15 years of age. In economic terms, this means a very high dependency ratio.